History in Malta's New National Curriculum Framework. (1st May 2013) - Vella, Yosanne
In February 2013 Malta's new national Curriculum, entitled 'A New National Framework for All' was launched. It was the end result of almost three years of meetings, debates, discussions, consolations and draft documents. This paper first gives a brief description of the historical background of Curricula in Malta, all of which eventually lead up to the present one, and then goes on to discuss specifically history in Maltese Curricula. Today it is no exaggeration to say that, of all school subjects history is the one which has undergone the most radical transformation as far as its pedagogy is concerned. History teaching in Malta now focuses on the learning of specific history skills and concepts, and analyses and interpretation of primary and secondary sources. However, history does not have a high status in the Maltese educational system and there were clear intentions in the initial stages of the creation of the new curriculum to eliminate the subject. This paper describes the advances in history pedagogy experienced in Malta in the past 20 years and the endeavours of the writer to retain history as a separate academic subject in the new curriculum.